Assessing the impact of the 2012 European Football Championships on the Polish economy. (1st January 2013) - Borowski, Jakub; Boratynski, Jakub; Czerniak, Adam; Dykas, Pawel; Plich, Mariusz; Rapacki, Ryszard; Tokarski, Tomasz
In this paper, we examine the impact of the UEFA EURO 2012™ on the Polish economy. The simulations are based on a dynamic computable general equilibrium (CGE) model and cover the years 2008–2020. We find that the main source of economic benefits is the acceleration of investments in transport infrastructure, which fosters growth of total factor productivity and the inflow of foreign direct investment. This contrasts with the results for more developed countries hosting major sporting events, where infrastructure effects are reported to be of less importance. Overall cumulative real GDP gains amount to 2.1% of the 2009 GDP level under the basic scenario.